Proteomic identification of serum proteins to induce osteoconductivity of hydroxyapatite - WANG, Yunting; YOSHIDA, Yutaka; KAMIIE, Junichi; SHIWAKU, Yukari; SUZUKI, Osamu; FURUYA, Maiko; YOKOTA, Kotone; KANETAKA, Hiroyasu; YOKOI, Taishi; KAWASHITA, Masakazu (Dental Materials Journal, 2021)
We performed proteomic analysis of rat serum proteins adsorbed on hydroxyapatite (HAp) and α-alumina (α-Al2O3) in order to identify proteins that specifically adsorb onto HAp and control cellular responses. Proteins with either or both molecular weight of 22–32 kDa and computed isoelectric point of 5.0–5.5 were preferentially adsorbed on HAp. In total, 182 proteins were adsorbed on both HAp and α-Al2O3, of which 14 were highly enriched on HAp, whereas 68 were adsorbed only on HAp. Therefore, 82 (14+68) proteins were further evaluated by bioinformatics and literature-based analyses. We predicted that hepatocyte growth factor and angiopoietin-like protein 3 (ANGPTL3) are candidate proteins responsible for the osteoconductivity of HAp. Although ANGPTL3 promoted the attachment and spreading of MC3T3-E1 cells, it did not promote their proliferation and differentiation. Our results suggest that specific adsorption of ANGPTL3 on HAp induced osteoconductivity by enhancing the attachment and spreading of osteoblasts.